Pengaruh Lingkungan Makroekonomi Terhadap Indeks Harga Saham Gabungan di Bursa Efek Indonesia - Sri Yuli Waryati; Andri Solaiman (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
This study aims to determine the effect of macro economic variables, namely: exchange rate (exchange rate), interest rates for Bank Indonesia certificates (SBI), inflation and growth of gross domestic product (PPDB) on the Composite Stock Price Index (IHSG). The population in this study is the entire period of time since the Indonesia Stock Exchange (IDX) was established, while the sample in this study is time series data for the period 2001 – 2020. Data collection techniques use documentation from monthly economic reports, IDX monthly statistics, reports from Bank Indonesia, the National Agency of Center for Statistics (BPS) and supporting data from books or several publications related to this research which are considered to be able to provide objective information through a network of websites. The analysis technique used is multiple linear regression. The results of this study indicate that the exchange rate has a significant effect on the JCI. The SBI interest rate has a significant effect on the JCI. Inflation has no significant effect on the JCI. PPDB has no significant effect on the JCI. Based on the results of the F test, it proves that the multiple linear regression model is feasible to use in this study (Goodness of Fit). The Adjusted R Square value of 0.848515 indicates that the Exchange Rate, SBI, Inflation, and PPDB variables have an effect of 84.8515% on the Composite Stock Price Index, while the rest is influenced by variables outside the study.